Effect of Sangyod Popped Rice Content on Quality of Cereal Bar Product - Sapbua, Dudsadee; Ting-nga, Nadsuda; Klaisribun, Sudarat; Cholmaitri, Chalida (Journal of Thai Food Culture, 2023)
The objective of this research studied the effect of Sangyod popped rice content on the quality of cereal bar products. Sangyods' popped rice was made by using a roasting method to avoid the frying process that would affect the quality of Sangyod rice pressed cereal bars. By using the amount of popped rice from Sangyod rice at 20, 30, and 40 percent of the total content of cereal bars. The sensory quality and physical quality of cereal bar products were studied. The result showed that 50 panelists in the sensory evaluation gave the highest statistically significant score on color preference for cereal bar products from Sangyod formula rice with popped rice content of 20 and 40 percent (p<0.05) 7.82±. 0.98, 8.08 ± 0.759 respectively. Sangyod formula rice with 20% popped rice content had the highest scores in terms of flavor, taste, texture, and overall liking, equal to 7.92 ± 0.80, 8.00 ± 0.90, 8.04 ± 0.88 and 8.18 ± 0.83, respectively (p<0.05). when increasing the amount of popped rice from Sangyod rice, the texture (hardness) decreased the cereal bar from Sangyod rice. The cereal bar product, using 20% popped Sangyod rice, the texture was the highest at 4,447.76 ± 90.67g force, which was related to the moisture content of 1.223 ± 0.148 percent. However, the Aw value of 0.287 ± 0.048 was not statistically different (p<0.05).